In God's shadow : politics in the Hebrew Bible - Walzer, Michael (Yale University Press, 2012)
Examines the laws, histories, prophecies, and wisdom of the ancient biblical writers and discusses their views on justice, hierarchy, war, the authority of kings and priests, and the experience of exile.
Keywords: Bible. -- Old Testament -- Criticism, interpretation, etc.; Bible. -- Old Testament; Bibel -- Altes Testament; Altes Testament.; Bible. -- Old Testament -- Criticism.; Politics in the Bible.; Politique dans la Bible.; RELIGION -- Biblical Studies -- Old Testament.; RELIGION -- Judaism -- Sacred Writings.; PHILOSOPHY -- Political.; Politics in the Bible; Politik; Politik.; Gesetz.; Gesellschaft.; Politics.; Criticism, interpretation, etc.